2018
DOI: 10.6026/97320630014075
|View full text |Cite
|
Sign up to set email alerts
|

Simian Virus 40 Large T Antigen as a Model to Test the Efficacy of Flouroquinolones against Viral Helicases

Abstract: Simian virus 40 large T-antigen (SV40 LT-Ag) is a 708 amino acid nuclear phosphoprotein. Among many functions of LT-Ag is its ability to perform as an ATPase-helicase, catalyzing the unwinding of viral genome during replication. The LT-Ag has been employed in the studies of helicase structure and function, and has served as a model helicase for the screening of antiviral drugs that target viral helicase. In this study, using in vitro enzyme assays and in silico computer modeling, we screened a batch of 18 fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Fluoroquinolones such as enoxacin are broad-spectrum synthetic antibiotics used in different clinical conditions like urinary tract-, respiratory-, and systemic infections 19,20 . Although quinolones are known to typically inhibit DNA replication by targeting bacterial DNA gyrases 21 , a growing body of evidence has revealed that some members of this family of antibiotics could also inhibit viral helicases, attenuate cytokine production and pro-in ammatory reactions 22 , and more importantly enhance the RNAi process as an in ammation-free innate immune defense against viral infections 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Fluoroquinolones such as enoxacin are broad-spectrum synthetic antibiotics used in different clinical conditions like urinary tract-, respiratory-, and systemic infections 19,20 . Although quinolones are known to typically inhibit DNA replication by targeting bacterial DNA gyrases 21 , a growing body of evidence has revealed that some members of this family of antibiotics could also inhibit viral helicases, attenuate cytokine production and pro-in ammatory reactions 22 , and more importantly enhance the RNAi process as an in ammation-free innate immune defense against viral infections 23 .…”
Section: Introductionmentioning
confidence: 99%